Formulation and Validation of Turmeric and Black Pepper Flavored Probiotics - Ranjith Arimboor; Zavier Thaliakuzhy; Nagamani Chintalarevi (University of Sultan Ageng Tirtayasa, 2023)
The beneficial or harmless microorganisms naturally found in the digestive tract have major roles in modulating the physiological functions of the host. Probiotics are live microbial feed supplement that helps to improve the intestinal microbial balance and thus imparts beneficial health effects. Spices are established sources of natural agents for food flavor and color. In this study, probiotic curd formulations containing varying contents of turmeric and black pepper were prepared and evaluated for the viability of aerobic bacteria during the shelf life of 15 days and consumer acceptability. Based on the results of the viability studies and sensory evaluation, acceptable compositions of a probiotics curd formulation flavored with turmeric and black pepper were arrived at. The formulation with 1.0 and 0.5 % turmeric and black pepper respectively was found to maintain the required levels of probiotic bacteria during the storage for 15 days and was well accepted in the sensory evaluation.